PENGARUH SOSIALISASI PERPAJAKAN TERHADAP KEPATUHAN PERPAJAKAN WAJIB PAJAK USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI SURAKARTA DENGAN PENGETAHUAN PERPAJAKAN SEBAGAI VARIABEL PEMEDIASI - Rizky Akbar Anwar; Muhammad Syafiqurrahman (InFestasi, 2016)
The purpose of this study is to analyze whether tax knowledge can mediate the influence of  tax socialization on  tax compliance in UMKM Surakarta, and to know the influence of  tax socialization on  tax compliance direectly. The sampel of this  research is UMKM as taxpayer listed in KPP Pratama Surakarta.  The method of analysis is quantitative method using multiple linear regression analysis. Classic asumption is used to get the best model of research. Variables os research are tax socialization as independent variable, tax compliance as the dependent variable, and tax knowledge as variabe mediation. The result of research indicate that tax socialization  has positive  influence tax significantly on tax knowledge  and tax compliance. Tax knowledge has positive influence significantly on tax compliance, and mediate influence of tax socialization on tax compliance for UMKM taxpayer in Surakarta.